2012
DOI: 10.4236/ijoc.2012.23033
|View full text |Cite
|
Sign up to set email alerts
|

A Facile and Efficient One-Pot Regioselective Synthesis of 2-Hydroxyalkyl Dithiocarbamates under Catalyst-Free Conditions

Abstract: A simple catalyst-free, and highly regioselective approach to 2-hydroxyalkyl dithiocarbamates is described which involves a one-pot reaction of various amines and carbon disulfide,CS 2 , with epoxides in ethanol at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This ligand continues to receive increased attention due to the presence of the carbon-sulfur bond which is useful in many products of biological and medicinal relevance [ 35 ]. This bond is also useful in the formation of organic intermediates with interesting chemistry [ 35 , 36 ]. Reports on their usage in protein folding, redox signaling and enzyme catalysis have been attributed to the strong nucleophilic character and peculiar properties of sulfur to undergo redox reaction [ 33 ].…”
Section: Chemistry Of Organotin(iv) Dithiocarbamatementioning
confidence: 99%
“…This ligand continues to receive increased attention due to the presence of the carbon-sulfur bond which is useful in many products of biological and medicinal relevance [ 35 ]. This bond is also useful in the formation of organic intermediates with interesting chemistry [ 35 , 36 ]. Reports on their usage in protein folding, redox signaling and enzyme catalysis have been attributed to the strong nucleophilic character and peculiar properties of sulfur to undergo redox reaction [ 33 ].…”
Section: Chemistry Of Organotin(iv) Dithiocarbamatementioning
confidence: 99%
“…Lewis acids such as gandolinium triflate-based tetrafluoroborate also successfully initiate the thiol-Michael addition reactions . Moghaddam et al demonstrated that a mixture of KF/Al 2 O 3 could yield an efficient ionic liquid to catalyze the thiol-Michael reaction while Movassagh et al examined ideal conditions under which the thiol-Michael addition reaction could proceed in the absence of a solvent. Gao et al further studied the efficiency of molecular iodine to successfully catalyze both aromatic and aliphatic thiol-Michael additions with 1,4-unstaturated carboxylic acids.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomena were consistent with small molecule reactions reported in the literature. [36][37][38][39][40] It is assumed that the in situ generated dithiocarbamic acid predominantly attacks the less hindered methylene of the epoxide to give the specific regioisomer. Meanwhile, in the 13 C NMR spectra of the model compound 5 and P1, the typical dithiocarbamate carbon peak at 197 ppm, the methylene carbon peak 9 connected to N atoms at 50 ppm and the methylene carbon peak 7 adjacent to S atoms at 38 ppm could be observed (Fig.…”
Section: Multicomponent Polymerizationmentioning
confidence: 99%
“…The mechanism of this three-component reaction has been well documented in the literature. [36][37][38][39][40] It is assumed that the unstable dithiocarbamic acid, initially generated from the amine and CS 2 , reacts with the epoxide leading to the formation of β-hydroxyl dithiourethane (Scheme S1 †). Moreover, the dithiourethane groups endow the polymers with non-conventional fluorescence properties and heavy metal adsorption ability.…”
Section: Introductionmentioning
confidence: 99%